European Association of Cardiovascular Imaging (EACVI) position paper: multimodality imaging in pericardial disease. (23rd September 2014) - Cosyns, Bernard; Plein, Sven; Nihoyanopoulos, Petros; Smiseth, Otto; Achenbach, Stephan; Andrade, Maria Joao; Pepi, Mauro; Ristic, Arsen; Imazio, Massimo; Paelinck, Bernard; Lancellotti, Patrizio
Abstract: Although pericardial diseases are common in the daily clinical practice and can result in a significant morbidity and mortality, imaging of patients with suspected or known pericardial disorders remain challenging. Multimodality imaging is part of the management of pericardial diseases. Echocardiography, cardiac computed tomography, and cardiovascular magnetic resonance are often used as complementary imaging modalities. The choice of one or multiple imaging modalities is driven by the clinical context or conditions of the patient. The scope of the present document is to highlight the respective role of each technique according to the clinical context in the diagnosis and management of pericardial diseases.